Sebuah PENGELOLAAN LIMBAH PLASTIK BERDASARKAN SISTEM HUKUM DI INDONESIA UNTUK MENCEGAH PENCEMARAN TANAH DI INDONESIA - Edy Suasono; Arsy Linardi; M Valdin Yudinata; Frida Juliany Hasibuan; Dedy Yunizar; Subur Yohana (Dialogia Iuridica, 2023)
The increasing use and consumption of plastic in this modern era is causing various problems for the environment. Plastic waste is difficult to decompose and its management is ineffective, resulting in soil pollution which is increasing day by day. The implementation of laws and regulations governing the management of plastic waste was found not to be running effectively. This article will review normatively the various rules regarding waste management, especially plastic waste in Indonesia. The review and analysis of this research was carried out using normative legal research methods by examining various relevant laws and regulations. The purpose of this research is to analyze how Indonesian environmental law regulates plastic waste management in Indonesia as well as the direction of regulatory policies related to plastic waste management in Indonesia to prevent soil pollution. The main findings reveal that there is still a lack of effectiveness in waste management and the absence of laws and regulations that specifically regulate the management of plastic waste. Furthermore, this article attempts to outline the policy direction of laws and regulations in managing plastic waste to prevent further soil contamination in Indonesia. The absence of special regulations for plastic waste management is an obstacle for the government to implement effective waste management.